Early diagnosis of Malan syndrome in an infant presenting with macrocephaly. Issue 11 (15th November 2022) - Seed, Lydia; G, Natasha; Prentice, Sarah; Chandershekar, Prathiba
Abstract : We present an infant with persistent macrocephaly and developmental delay. There is a wide range of differential diagnoses for this presentation, including many rare genetic conditions. Here, a diagnosis of Malan syndrome was made—a rare overgrowth syndrome caused by haploinsufficiency of NFIX and features affecting the neurological and musculoskeletal systems. Improvements in genomic medicine technologies and clinical services have revolutionised the way clinicians diagnose rare diseases. We highlight the importance of early genetic testing, particularly if there are red flag features such as developmental delay, and the need for a coordinated strategy to improve the management of rare diseases like Malan syndrome.